Distancing the Components of Attributive Phrases in Artistic Speech - K. Ya. Seagal (Научный диалог, 2020)
The problem of distancing the components of attributive phrases as a syntactic and stylistic phenomenon in artistic speech is considered. The relevance of the study lies in the fact that the issue of preserving the syntactic form of the phrase while distancing its components has not yet been resolved and the mechanism for creating a stylistic technique based on the distance of the components of attributive phrases has not been clarified. The novelty of the study lies in the approach that takes into account the interaction of syntax and stylistics in the functioning of the same speech means - attributive phrases in conditions of distance. On the material of the corpus of speech examples selected from the novel by M. A. Sholokhov “Quiet Don”, it is shown that when distancing the attributive phrase, ceasing to be integral, does not lose its syntactic form. The syntactic properties that occur in attribute phrases in a distancing form of their existence are generalized. When describing the stylistic method of distancing, it is stated that it is intended not only to concentrate on the attribute information about the subject, but also to testify to the signifying “reload” that the attribute phrase undergoes when moving forward its dependent component in the sentence-utterance.